Could trees change future behaviour in xylogenesis to improve fitness based on past and current conditions? A tropical case of study (Research, Society and Development, 2022)
Carbon allocation is the Achilles' heel of forest models, due to the difficulty to predict responses induced by environmental changes. Structural-functional models involve the plant's strategy to split its resources between organs and functions. An important functional characteristic is xylem architecture, which is connected to water use strategy and plant productivity besides one of the most important C-sink (that absorbs carbon). Our goal is to use the information present in the tree rings of Schizolobium parahyba, to expand the possibilities of teleonomic approaches in structural-functional models of tree species. In a comparative xylem rings analyses, we established relationships among specific gravity, vessel traits as hydraulic conductivity potential, double wall thickness, and autofluorescence intensity of lignin. The analyses showed that growth ring characteristics seem to have been modulated not only by water availability of the period of wood formation but also by the water availability of previous years. This relationship would be occurring due to the greater capacity of accumulation of reserve carbohydrates in years whose climatic conditions were favourable. This pattern of behaviour entails the formation of two distinct growth ring patterns, one with high and the other with low structural cost. This case study shows that the species can change future behaviour in xylogenesis to improve fitness based on past and current conditions. Our study may help to extend the possibilities of teleonomic approaches in structural-functional models of tree species, which will assist in a greater understanding of how trees balance their carbon allocation in wood according to changes in the environment.